Maternal tetanus at the university college hospital in Ibadan Nigeria: a 15-year retrospective analysis (2008)
Objective To determine the characteristics of women with maternal tetanus, pattern of presentation and outcome of management. Methods A total of 19 women were managed with maternal tetanus between 1990 and 2005 from the University College Hospital in Ibadan Nigeria. A retrospective study was performed. The medical records of all women managed as a case of maternal tetanus were retrieved from the central record department of the hospital. The pattern of presentation, characteristics of women, the duration of hospital admission, tetanus toxoid immunization, and outcome of care were measured. Results The records of 18 women managed were analyzed. The mean age at presentation was 25.2 ± 5.3 years. The patients were mostly single, nulliparous and had primaryschool education. The maternal tetanus cases seen mainly complicated induced abortion while 5 and 2 other cases were due to childbirth complication and leg wound respectively. The portal of entry of the remaining 3 cases could not be ascertained. None of the patient managed had complete immunization schedule. The average duration of admission was 11.2 ± 6.7 d. Five women had intensive care with 3 of them requiring ventilatory support. The case fatality rate was 66.7%. The only factor that significantly improved survival was presence of generalized spasm at presentation (P=0.006) Conclusion The occurrence of maternal tetanus is a reflection of low quality of health care delivery and lack or inefficient routine immunization coverage in any community